2014
DOI: 10.1007/s00261-014-0080-6
|View full text |Cite
|
Sign up to set email alerts
|

Multimodality imaging of splenic lesions and the role of non-vascular, image-guided intervention

Abstract: Splenic lesions are often incidentally detected on abdominal-computed tomography (CT), ultrasound, or magnetic resonance imaging (MRI), and these can pose a diagnostic challenge in patients with suspected or known malignancy. This review will discuss the multimodality imaging features of various benign and malignant splenic pathologies including trauma, infection, infarct, granulomatous disease, benign neoplasms such as hemangioma, hamartoma, and littoral cell angioma, cystic entities such as peliosis, splenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…Splenic metastases show usually minimal to heterogeneous centripetal enhancement that depends on the primary neoplasm. 17 Pathological findings of splenic metastases have also been reported. 18 However, we found no report concerning the peritumoral fibrous capsule of splenic metastases.…”
Section: Only 19 Cases Of Splenic Ipt-like Fdcts or Iptsmentioning
confidence: 95%
“…Splenic metastases show usually minimal to heterogeneous centripetal enhancement that depends on the primary neoplasm. 17 Pathological findings of splenic metastases have also been reported. 18 However, we found no report concerning the peritumoral fibrous capsule of splenic metastases.…”
Section: Only 19 Cases Of Splenic Ipt-like Fdcts or Iptsmentioning
confidence: 95%
“…Lesions that are very likely to be metastases require further intervention. However, it is difficult to diagnose splenic lesions accurately using multimodality imaging techniques, including CT, ultrasound and magnetic resonance imaging (12). The lesion in the present case may have been infectious, such as an abscess or other malignancy, as it did not respond to chemotherapy compared with the intrathoracic lesions.…”
Section: Discussionmentioning
confidence: 84%
“…Gutzeit A et al [12] showed a case of SANT diagnosed by means of ultrasoundguided core needle biopsy without complications. Recent studies demonstrated lower complication rates in image-guided splenic biopsy [13]. On the other hand, it should be noted that some cases of SANT can gradually increase in size during the follow-up period, despite its benign etiology [10].…”
Section: Discussionmentioning
confidence: 99%